Toksyczny wpływ trzech związków ołowiu na daphnia magna straus i dugesia tigrina girard = Toxic effect of three lead compounds on daphnia magna straus and dugesia tigrina girard - Piontek, Marlena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Experiments were done on two freshwater species, Daphnia magna Straus and Dugesia tigrina Girard. The toxic effects on 3 toxic compounds, lead nitrate, lead chloride (mineral substances) and lead acetale (organic compound) were used in the studies of acute intoxication. The sensitivity of two methods, test with cut planarians and test with Daphnia magna were compared.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)